Pendidikan Anak Usia Dini dalam Perspektif Islam Pada Pemerintahan Era Reformasi - Ali Rohmad (Tarbiyah Departement collaboration with AMCA, 2013)
Golden childhood education (the golden age) can be the basis of the formation of human character that plays an important role again decisive for the future of society, nation, and state. In reality, an Indonesian citizen awareness on this subject have been formed during the reign of the old order and the new order were characterized by the establishment of Kindergarten (TK), Raudlatu Athfal (RA), dan Bustanul Athfal (BA). The presence of government reform era looked implement its own policy which is expected to bring more significant changes to early childhood education. Academically, this can all be viewed as a unique event again interesting to study further.